EXPERTISE ON POLITICALLY CONNECTED BOARD AND FIRM PERFORMANCE - Anak Agung Gede Krisna Murti (Jurnal Bisnis dan Akuntansi, 2024)
Political connections have become a prevalent practice in both developing and developed countries, often involving close relationships between company owners, Boards of Commissioners (BOC), and Boards of Directors (BOD) with government leaders, legislators, politicians, and former high-ranking officials. This practice aims to leverage resources derived from these political connections, in line with resource dependence theory. However, the impact of political connections on companies can be both positive and negative. Potential benefits include access to resources, favorable policies, financial aid, and valuable information, but there are also risks of poor accounting performance and exploitation. Research indicates that politically connected boards tend to be less professional and face higher bureaucratic influence. From an agency theory perspective, lower board expertise may reduce monitoring effectiveness and company performance. The role of political connections in financial performance might be influenced by the lack of expertise among boards with political ties. These boards may have varying professional backgrounds, including politicians, professionals, scientists, bureaucrats, or business practitioners, and may simultaneously provide network and resource benefits while performing effective monitoring and management. This study aims to evaluate whether boards with both political connections and expertise have an impact on company performance and to investigate the interaction between board expertise and political connections on firm performance. The research uses data from companies listed on the Indonesia Stock Exchange to provide evidence on the influence of board expertise and political connections at both the individual board member and company levels.